Điều khiển thích nghi vị trí trên cơ sở kỹ thuật vi xử lý Phần I: Hệ thống điều chỉnh vị trí nhờ quan sát và phản hồi trạng thái - Thoa, Pham Huy (Journal of Computer Science and Cybernetics, 2018)
In order to investigate different position control algorithms for numerical controlled machines and robots, a positional control system was built on the base of a microcomputer. In part I, the paper presents the observer algorithm for state variable estimation and the state variable feedback control algorithm applied to the position control of a particular machine-table. With the hardware and software structure of the microcomputer based digital system described in this paper different control algorithms can be realized flexibly. The position control problem for the plant with variations or uncertainties of parameters and load characteristics will be reported in part II.